Pemanfaatan Lemna minor L. dan Hydrilla verticillata (L.f.) Royle untuk Memperbaiki Kualitas Air Limbah Laundry - Tri Rima Setyawati, Maya Safitri Mukarlina (Universitas Tanjungpura, 2019)
Lemna minor and Hydrilla verticillata are types of water plants that have the potential to have the ability to process and improve the quality of polluted water. The purpose of this study is to determine the ability of Lemna minor and Hydrilla verticillata in improving the quality of laundry wastewater. The study used a completely randomized design (CRD) method with six treatments and three replications. The study was carried out on test media in the form of 5 liters of laundry wastewater with L. minor (L) 100 g, H. verticillata (H) 100 g, and combination treatment of both plants (L1H1, L1H2, L2H1) in weight L1H1 (50 g : 50 g), L1H2 (33 g : 67 g) and L2H1 (67 g : 33 g) for 14 days after acclimation for one week. The combination of L. minor and H. verticillata with a ratio of 1: 2 was able to reduce the highest Total Suspended Solid (TSS) and Total Dissolved Solid (TDS) of laundry wastewater with a decrease of 52.87% and 4.02% and increase dissolved oxygen (DO) of 7.13 mg/L. The highest decrease in chlorine occurred in L. minor and H. verticillata treatments with a ratio of 1:1 of 0.110 mg/L. All treatments of L. minor and H. verticillata both singly and in combination have not been able to reduce the phosphate content in laundry wastewater on day 14 of treatment.